2011
DOI: 10.1039/c1sm05760j
|View full text |Cite
|
Sign up to set email alerts
|

The growth of micelles, and the transition to bilayers, in mixtures of a single-chain and a double-chain cationic surfactant investigated with small-angle neutron scattering

Abstract: Self-assembly in aqueous mixtures of a single-chain (DTAB) and a double-chain cationic surfactant (DDAB) has been investigated with small-angle neutron scattering (SANS). Small oblate spheroidal micelles formed by DTAB grow with respect to width and length to form mixed ellipsoidal tabletshaped micelles as an increasing fraction of DDAB is admixed into the micelles. The growth behaviour of the micelles is rationalized from the general micelle model in terms of three bending elasticity constants spontaneous cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 35 publications
7
25
1
Order By: Relevance
“…The growth behavior hNi / / 1=2 mic , derived by using mole fraction rather than volume fraction in the expression for the entropy of mixing, implies a maximum polydispersity equal to r N /hNi = 1/ ffiffiffi 2 p % 0.71. The latter result is inconsistent with experimental observations that r N /hNi is frequently found to be close to or larger than unity for long rodlike or wormlike micelles [10,47,48,65,66]. A relative standard deviation exceeding unity implies an extent of growth stronger than predicted by the spherocylindrical micelle model [cf.…”
Section: Polydispersity Of Micellescontrasting
confidence: 69%
“…The growth behavior hNi / / 1=2 mic , derived by using mole fraction rather than volume fraction in the expression for the entropy of mixing, implies a maximum polydispersity equal to r N /hNi = 1/ ffiffiffi 2 p % 0.71. The latter result is inconsistent with experimental observations that r N /hNi is frequently found to be close to or larger than unity for long rodlike or wormlike micelles [10,47,48,65,66]. A relative standard deviation exceeding unity implies an extent of growth stronger than predicted by the spherocylindrical micelle model [cf.…”
Section: Polydispersity Of Micellescontrasting
confidence: 69%
“…Similar results have been reported by many workers. Bergstrom and Pederson have reported the micelle‐to‐bilayer transition along with the coexistence of micelles, disk like aggregates and vesicles induced by changes in surfactant composition …”
Section: Resultsmentioning
confidence: 99%
“…However, only prolatespheroidal shape was considered in the data analyses.More recently, the growth behaviour with respect to surfactant composition of mixed DTAB/DDAB micelles in absence of added salt was investigated with SANS by the present authors. [17] It was found that the quality of the model fits could be significantlyimprovedusing a model for general ellipsoids. In accordance, it was concluded that rather small oblate spheroidal DTAB micelles grow slightly in width, and more pronouncedly in the length direction, to form general ellipsoidal micelles as an increasing amount of DDAB was incorporated in the surfactant aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…When the ellipsoidal micelles have a half axis related to length equal to c = the micelles in a narrow regime. From model calculations based on the Poisson-Boltzmann mean field theory, we were able to determine the mole fraction of DDAB in the self-assembled interfacial aggregates (i.e., micelles and bilayers) at the micelle-tobilayer transition equal tox = 0.41 in H 2 O (with static light scattering) [18] and x = 0.48 in D 2 O (with SANS) [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation